(untitled) (Colombia Medica, 2012)
Background:Cancer is being increasingly diagnosedthroughout the world, possibly related to increased lifeexpectancy, greater exposure to known carcinogens,increased healthcare coverage, application of screeningprograms, and active search for cases. In the UnitedStates, 1-million new cases are diagnosed with more than500,000 deaths per year. The costs of attention and worklost are very high. In Colombia, this pathology hasbehaved in similar manner, constituting a general publichealth problem. In 2004, in Manizales 653 new cases werediagnosed.Objective:To describe the characteristics of thepopulation with cancer diagnosis treated in the InstitutoOncológico ION SA of Manizales, Caldas, Colombia,since its foundation on March/1995 to December/2004.Materials and methods: Some5000 patients weretreated in the Institution were included from 1995 to2004. The demographic and clinical variables were analyzedto establish the frequencies of presentation and to knowthe main aspects of the study given in the Institution andthe most important results about the treatment withdifferent therapeutic modalities.Results:Median age of 57 years +17.3, female (65.6%),urban origin (90.2%). The main occupational categorywas «Various occupations» (61%) followed by «Technical»(12.1%). The most common diagnoses were breast cancer18.7%, cervical cancer 13.1%, lymphomas 7.7%, colo-rectal cancer 6.4%, and gastric cancer 4.7%. Most patients(69.1%) consulted after two months of their firstsymptoms. The III and IV clinical stages were the mostfrequent at diagnosis. According to the Karnofsky scale,the functional capacity was good at the beginning oftreatment. Therapeutic modalities were surgery,chemotherapy, and radiotherapy. The toxicity of thetreatments revealed a total frequency of 11.3% (567/5,000). The overall survival at 5 years for men and womenwas 61.2% and 72.3%, respectively (p<0.05).Conclusions:The clinical and epidemic profile ofthe patients attended in the ION SA in Manizales, Co-lombia, does not differ in its general aspect from othercancer studies, other analytic studies must be conductedto determine associations among them to help to bestunderstand the Oncologic phenomenon of our Insti-tution.